Measurement of aerodynamic performance of propeller for unmanned aerial vehicle (UAV) application - Muhammad Rahimi Malek, 1994- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2017